Knowledge and Access to Adolescent Reproductive Health Information in Indonesia - Saparini, Suci; Simbolon, Demsa; Ningsih, Lisma (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2024)
Background: According to research, Indonesia faces challenges as a result of a low level of knowledge of adolescent reproductive health (ARH) due to limited exposure to information media. Access to information and knowledge among adolescents influences their risky behaviors towards ARH. This quantitative and cross-sectional study aims to examine the relationship between ARH behaviors and access to information and knowledge among unmarried Indonesian adolescents aged between 10 and 24, both male and female. This study collected secondary data from the 2019 Program Performance and Accountability Survey (PPAS). The independent variables were access to information and knowledge about ARH, whereas the dependent variables were ARH behaviors. In addition, the confounding variables were adolescent characteristics (i.e., age, gender, and level of education) and family characteristics (i.e., social economy and location of residence).Method: The data were analyzed using a multivariate logistic regression statistical test. Results: The findings revealed a significant relationship between ARH behaviors and access to information about ARH from various information media (p-value = 0.001) as well as between ARH behaviors and knowledge of ARH (p-value = 0.001). The findings suggested that health promotion for ARH should be enhanced by providing access to information from various social media commonly used by adolescents, which can increase knowledge about ARH and influence adolescent behaviors toward good reproductive health.